2016
DOI: 10.18632/oncotarget.10399
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyl-terminal truncated HBx contributes to invasion and metastasis via deregulating metastasis suppressors in hepatocellular carcinoma

Abstract: Hepatitis B virus (HBV) X protein (HBx), a trans-regulator, is frequently expressed in truncated form without carboxyl-terminus in hepatocellular carcinoma (HCC), but its functional mechanisms are not fully defined. In this report, we investigated frequency of this natural HBx mutant in HCCs and its functional significance. In 102 HBV-infected patients with HCC, C-terminal truncation of HBx, in contrast to full-length HBx, were more prevalent in tumors (70.6%) rather than adjacent non-tumorous tissues (29.4%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…HBx has been well documented with respect to playing an oncogenic role in HCC development. There is evidence available indicating that HBx promoted HCC cell invasion and metastasis by down‐regulating Wnt‐5α and up‐regulating MMP10 (Li et al ., 2016; Sze et al ., 2013). HBx serves as a transcriptional regulator of many oncogenes and tumor suppressor genes.…”
Section: Discussionmentioning
confidence: 99%
“…HBx has been well documented with respect to playing an oncogenic role in HCC development. There is evidence available indicating that HBx promoted HCC cell invasion and metastasis by down‐regulating Wnt‐5α and up‐regulating MMP10 (Li et al ., 2016; Sze et al ., 2013). HBx serves as a transcriptional regulator of many oncogenes and tumor suppressor genes.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) ranks the sixth most common cancer and the third cause of cancer-related mortality worldwide [ 1 , 2 ]. In Asia and sub-Saharan Africa areas, over 5% of the populations suffered chronically infected chronic hepatitis B virus (HBV) infection, which could reflect the elevated prevalence of HCC [ 1 , 3 5 ]. In china, the estimated new cases and deaths for HCC were 466.1 and 422.1 thousands, respectively [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that the random integration of HBV genome may led to the C-terminal truncation of HBx (HBx-ΔC, usually loss the C-terminal 27-30 aa) 28 . The HBx-ΔC frequently expressed in HBV-associated liver tumors, and play a important role in facilitating hepatocarcinogenesis 29 , 30 . Therefore, we further tested the reactivity of 9D11 in detections of natural HBx mutants via Western blot analyses of cell lysates of matched pair tissues derived from 5 additional CHB related HCC patients (patient 4 to 8).…”
Section: Resultsmentioning
confidence: 99%